2023
DOI: 10.1002/anie.202216923
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Enantioselective Doyle–Kirmse Reaction of Azide‐Ynamides via α‐Imino Copper Carbenes

Abstract: [2,3]‐Sigmatropic rearrangement reaction involving sulfonium ylide (Doyle–Kirmse reaction) generated from metal carbenes represents one of the powerful methods for the construction of C(sp3)−S and C−C bonds. Although significant advances have been achieved, the asymmetric versions via the generation of sulfonium ylides from metal carbenes have been rarely reported to date, and they have so far been limited to diazo compounds as metal carbene precursors. Here, we describe a copper‐catalyzed enantioselective Doy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 109 publications
1
9
0
Order By: Relevance
“…Generated from 1-sulfonyl-1,2,3-triazole, α-imino rhodium carbene was utilized as 1,3-dipole in construction of various ring systems. [6][7][8][9] Intramolecular group migration of carbene is an effective strategy to produce multiple-functionalized zwitterion. [10] Our group developed a migration-annulation strategy to synthesize valuable (hetero)cyclic compounds.…”
mentioning
confidence: 99%
“…Generated from 1-sulfonyl-1,2,3-triazole, α-imino rhodium carbene was utilized as 1,3-dipole in construction of various ring systems. [6][7][8][9] Intramolecular group migration of carbene is an effective strategy to produce multiple-functionalized zwitterion. [10] Our group developed a migration-annulation strategy to synthesize valuable (hetero)cyclic compounds.…”
mentioning
confidence: 99%
“…1). 1,2 We developed transition metal-promoted molecular transformations of ynamides for the synthesis of valuable compounds, including biologically active natural products. 3 In the half century since Viehe et al first reported the synthesis of ynamides in 1972, 4 ynamides with various electron-withdrawing groups and substituents have been synthesized.…”
mentioning
confidence: 99%
“…6 Nowadays, annulation of α-imino rhodium carbenes has emerged as one of the most versatile methods for the construction of various nitrogen-containing heterocycles. [7][8][9][10][11] In continuation of our interest in the chemistry of α-imino rhodium carbenes and heterocycle synthesis, the synthesis of 3-aminoquinolines via rhodium-catalyzed transannulation of 1-sulfonyl-1,2,3-triazole with 2-aminobenzaldehyde was designed (Scheme 1C). In this proposal, N-H insertion of rhodium carbene with 2-aminobenzaldehyde was followed by cyclization and aromatization.…”
mentioning
confidence: 99%
“…6 Nowadays, annulation of α-imino rhodium carbenes has emerged as one of the most versatile methods for the construction of various nitrogen-containing heterocycles. 7–11…”
mentioning
confidence: 99%
See 1 more Smart Citation